2011
DOI: 10.1111/j.1365-3148.2011.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey to assess transfusion medicine education needs for clinicians

Abstract: Additional training in TM would be beneficial to and welcomed by physicians in all training levels in all specialties. Innovative specialty-specific educational programmes need to be developed and tested to ensure efficacy and durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
64
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 14 publications
8
64
2
Order By: Relevance
“…Studies have been conducted in countries such as the United States, United Kingdom, Tunisia, Canada and Iran to assess the degree of knowledge about transfusion medicine of newly graduated doctors; all studies reported lower than expected results 9, 10, 11, 12. In a poll conducted in 86 medical schools in the United States, most had less than three hours in the curricular grid dedicated to transfusion medicine 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted in countries such as the United States, United Kingdom, Tunisia, Canada and Iran to assess the degree of knowledge about transfusion medicine of newly graduated doctors; all studies reported lower than expected results 9, 10, 11, 12. In a poll conducted in 86 medical schools in the United States, most had less than three hours in the curricular grid dedicated to transfusion medicine 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of transfusion decisions are made by physicians and surgeons without formal training in TM. Their practices are based on individual clinical experiences and they are unaware of the best methods of practice and recent developments in the literature [2]. The majority of blood banking training barring TM post graduate programme, is given in pathology residency programs.…”
Section: Introductionmentioning
confidence: 99%
“…A validated transfusion medicine exam would enable a better assessment of educational methods, trainee knowledge, and areas for improvement. While transfusion medicine exams have been published, they were not designed or validated using accepted psychometric techniques . As noted in an editorial on the development of one of the more recent of these exams, “several critical points about the experimental design and conduct of the study raise questions about the quality of the results and/or data and whether all conclusions and recommendations are truly warranted.” In this study, we used rigorous analytical methods to develop a validated transfusion medicine exam.…”
mentioning
confidence: 99%